PERANCANGAN ROBOT PENYORTIR BENDA BERWARNA BERBASIS MIKROKONTROLER - Lyri Martin Simorangkir (Saintia Fisika, 2013)
Utilization of today's technology industry demands development in terms of accuracy, speed fully automated. One of the industry's use of technology such as the sorting of objects. Has designed a robot sorter 16 objects color based on microcontroller ATMega8535. The purpose of this study as a sorter object by color automatically with DT- Sense Color. Overall design of the robot consists of 4 (four) as the servo motor actuator arm, one (1) servo motor as the driving conveyors, DT-Sense Color as color sensors, Infra Red, Infra Red Adjustable, ATMega8535 microcontroller, LCD 2x16 and respectively 16th place for the color of objects to be sorted out. The method used for positioning objects laying on the color space used by the mapping method arena. The design which has been made ​​to produce 16 color sorting objects successfully read in conjunction with programs designed. Keywords: Color Sensor, Robot Arm, Microcontroller.